2022
DOI: 10.31083/j.rcm2309292
|View full text |Cite
|
Sign up to set email alerts
|

Longer Hospitalizations and Higher In-Hospital Mortality for Acute Heart Failure during the COVID-19 Pandemic in Larger vs. Smaller Cardiology Departments: Subanalysis of the COV-HF-SIRIO 6 Multicenter Study

Abstract: Background:The coronavirus disease-2019 (COVID-19) pandemic is surging across Poland, leading to many direct deaths and underestimated collateral damage. We aimed to compare the influence of the COVID-19 pandemic on hospital admissions and in-hospital mortality in larger vs. smaller cardiology departments (i.e., with ≥2000 vs. <2000 hospitalizations per year in 2019). Methods: We performed a subanalysis of the COV-HF-SIRIO 6 multicenter retrospective study including all patients hospitalized in 24 cardiology d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In Poland, in 24 Cardiology Departments, the total number of hospitalizations in 2020 decreased by 28.6% compared to the year before [9]. The reduction in hospital admissions happened regardless of department size [10]. This trend can be ascribed not only to public sentiment associated with the pandemic but also to governmental regulations.…”
Section: Discussionmentioning
confidence: 95%
“…In Poland, in 24 Cardiology Departments, the total number of hospitalizations in 2020 decreased by 28.6% compared to the year before [9]. The reduction in hospital admissions happened regardless of department size [10]. This trend can be ascribed not only to public sentiment associated with the pandemic but also to governmental regulations.…”
Section: Discussionmentioning
confidence: 95%
“… 45 , 46 Additionally, cardiac consultations, electrophysiology procedures, 47 and hospitalization for HF declined 48 during the pandemic, potentially influencing the outcome of these patients. 49 , 50 Furthermore, during the first year of the pandemic, US census regions were disproportionately affected by the COVID‐19 pandemic, leading to a different mortality excess in the country. 51 Specifically, the higher COVID‐19 related mortality rates were registered in the South due to a higher infection rate, limited access to health care resources, differences in the prevalence of underlying conditions associated with higher mortality rates, such as arterial hypertension, diabetes, and obesity as well as to different implementation of COVID‐19 preventive strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The length of hospital stay was similar in both groups, but the 30-day mortality for AHF was significantly higher during the COVID-19 pandemic vs. before accounting 21% vs. 11%, respectively (risk ratio: 1.9; 95% CI 1.09–3.3). In a previous subanalysis of the COV-HF-SIRIO-6 multicenter study, longer hospitalizations were found (9.6 vs. 6.6 days; p < 0.001) and higher in-hospital mortality (10.7% vs. 3.2%; p < 0.001) was found for AHF during the COVID-19 pandemic in larger vs. smaller cardiology departments [ 32 ]. As reported in a retrospective study including 13,484 patients hospitalized in a German network of 67 hospitals, in-hospital mortality for AHF was higher during the COVID-19 pandemic vs. time-related period in 2019 (7.3% vs. 6.0%; p = 0.02) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%